Validation and reproducibility of an LC–MS/MS method for emixustat and its three deaminated metabolites in human plasma. (16th October 2018) - Podoll, Terry; Geisler, Lisa; Parys, Michael Van; Hanson, Glenn; Reid, Michael J
Aim: A sensitive method to quantify emixustat and its rapidly formed three major deaminated metabolites in human plasma was necessary to determine exposure in clinical trials.Methods: An LC–MS/MS method was validated for accuracy and precision, linearity, carry over, selectivity, recovery, matrix effects, hematocrit effects and stability.Results: A quantitative procedure for the determination of emixustat, ACU-5116, ACU-5124 and ACU-5149 in human plasma over the concentration range of 0.0500/1.00/1.00/1.00–10.0/1000/1000/1000 ng/ml, was successfully validated and has been used to successfully analyze samples in three clinical trials. Incurred sample reanalysis was performed for all four analytes in each study with >92% of the repeat results and original results within 20% of the mean of the two values.